Place attractiveness and tourists’ walking experience in the city of Kuala Lumpur, Malaysia - Ujang, Norsidah (2014)
Based on Kuala Lumpur Structure Plan 2020, planning and tourism development in Malaysia has focused on the provision of facilities, infrastructure services and creating programs for the use of tourists. According to Anuar et.al (2013) space, activities, and products have been developed and implemented by the authority for the purpose of conceiving a tourist-friendly destination. Among the emphasis are on conservation projects beautification and pedestrian walkways. This paper examines the impact of place attractiveness on tourists' walking experience in three areas of attraction in the city. A questionnaire survey (N=419) and face to face interviews (N=12) were conducted with local and foreign visitors. Evidence gathered from direct observations of the streets' setting and activities support the analysis. The study found that the visitors were fairly satisfied with their experience of the places with fairly strong attachment to the places. The results demonstrated that the traditional streets are successful in sustaining its attraction for the target users despite growing complaints at the loss of ‘charm' (identity) of the main shopping streets due to the inappropriate concept and image of the newly completed street improvement programme. However, results have indicated positive responses on distinctiveness of culture and diversity of trading activities within the areas. Tourists were attracted to the image of buildings (an iconic image) and open spaces, food, local culture and traditional shopping places. There is a lack of identification on landscape and greenery as well as architectural images. The results also indicate a significant difference in the responses between local and foreign visitors. By improving the attractiveness of tourist places, visitors are expected to have more enjoyable walking experience and greater potential for return visit to the places of interests.